2018
DOI: 10.3390/w10010037
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Primary, Secondary, and Tertiary Wastewater Treatment Processes on Antibiotic Resistance Gene (ARG) Concentrations in Solid and Dissolved Wastewater Fractions

Abstract: Abstract:Wastewater treatment plants (WWTPs) have been identified as potential sources of antibiotic resistance genes (ARGs) but the effects of tertiary wastewater treatment processes on ARGs have not been well characterized. Therefore, the objective of this study was to determine the fate of ARGs throughout a tertiary-stage WWTP. Two ARGs, sul1 and bla, were quantified via quantitative polymerase chain reaction (qPCR) in solids and dissolved fractions of raw sewage, activated sludge, secondary effluent and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…Today, newer waste treatment facilities including plasma pyrolysis, encapsulation, inertization have been introduced, to replace older facilities such as incineration as toxic fumes (dioxins and furans) are produced which are harmful to both health and environment. Wastewater treatment plants (WWTP) were also thought to remove the antimicrobial resistance genes during the processing of the waste, which is being generated from the hospitals [5][6][7]. In developing countries, however, wastewater treatment plant is still considered costly [2].…”
Section: Introductionmentioning
confidence: 99%
“…Today, newer waste treatment facilities including plasma pyrolysis, encapsulation, inertization have been introduced, to replace older facilities such as incineration as toxic fumes (dioxins and furans) are produced which are harmful to both health and environment. Wastewater treatment plants (WWTP) were also thought to remove the antimicrobial resistance genes during the processing of the waste, which is being generated from the hospitals [5][6][7]. In developing countries, however, wastewater treatment plant is still considered costly [2].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the concentrations and removal rates of ARB and ARGs in different waste processing and wastewater treatment processes are varied, depending on the mitigation step, and also the format, type and measurement methods used (see [42][43][44][45][46][47][48][49][50]). For example, limited ARG and ARB reduction data exist on the most basic mitigation options, such as the value of moving from OD to improved basic sanitation.…”
Section: Relative Benefit Of Different Ar Sanitation Interventionsmentioning
confidence: 99%
“…The ARGs used for comparisons here were chosen because they are measured in most treatment studies by a common analytical method, quantitative Polymerase Chain Reaction. For our study, we chose specific ARG data from nine manuscripts that examined full-or field-scale systems [42][43][44][45][46][47][48][49][50]. Other manuscripts were considered, but our goal was to contrast ARG conditions and removal rates only in "real" sanitation systems.…”
Section: Relative Benefit Of Different Ar Sanitation Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of antimicrobialresistant bacteria presents a major threat to public health because it reduces the effectiveness of antimicrobial treatment, leading to increased morbidity, mortality, and healthcare expenditure (Lyimo, Buza, Subbiah, Smith, & Call, 2016). Studies have shown the prevalence of antibiotic-resistant pathogens in wastewaters discharged into water bodies (Guardabassi, Petersen, Olsen, & Dalsgaard, 1998;Pruden et al, 2006;Quach-Cu, Herrera-Lynch, Marciniak, & Adams, 2018;Reinthaler et al, 2003), leading to the challenges in antimicrobial therapy. A few authors, in their antibiotic-resistance comparative review using wastewaters from a hospital and a pharmaceutical plant, disclosed that the wastewater from the pharmaceutical plant had increased prevalence of antibiotic resistance among Acinetobacter species (Guardabassi et al, 1998).…”
Section: Introductionmentioning
confidence: 99%